Mapping men's anticipations and experiences in the reproductive realm: (in)fertility journeys. - Hinton, L; Miller, T (2013)
This paper examines men's experiences of fertility/infertility against a backdrop of changing understandings of men's role in society and medical possibilities. It presents findings from two qualitative research projects on men's experiences of engagement with reproductive health services as they sought to become fathers and anticipate impending fatherhood. The findings from both projects provide insights into men's experiences of (in)fertility and their engagement with services set against cultural ideals of masculinity. Discussions of reproduction have historically focused most centrally upon women's bodies and maternal processes, leaving little space for consideration of men's experiences and perspectives. While women's experiences of infertility/fertility have been characterized in relation to productive or faulty biological processes, male infertility has been largely invisible and male fertility typically assumed. This context provides a difficult terrain for men in which to contemplate the potential of not being able to father a child. The findings discussed in this paper illuminate the ways in which men talk about and make sense of their reproductive journeys. In doing so, it challenges current understandings of masculinity and reproductive bodies and highlights the need to rethink how men are treated in reproductive spheres and how services to men are delivered.